Phytochemical Studies in Eleven Species of Ferns from Satara District of Maharashtra (India) - Meena Dongare3, Bharat Jadhav1, Shakil D. Shaikh2* and (Recent Research in Science and Technology, 2011)
The present study was carried out with respect to phytochemical analysis such as chlorophylls, carotenoids and polyphenols contents in the eleven species of ferns from the Satara district of Maharashtra. The different species showed variation in their photosynthetic pigments. the different species shows increase in photosynthetic pigment during vegetative stage and decreases during mature stage. The decrease in photochemicals during reproductive stage may be due to sporangium formation which may create a stress during the maturation and increasing the amount of phenols.